ANALISIS KEPUTUSAN PEMBIAYAAN TALANGAN HAJI PADA NASABAH DI PT. BPRS METRO MADANI - Nur Fitriyaningsih; Jawoto Nusantoro; Angga Kurniawan (Universitas Muhammadiyah Metro, 2021)
This research is a qualitative research that aims to analyze the decision of financing hajj bailouts for customers. This research was conducted at PT BPRS Metro Madani, with data sources consisting of primary data sources. And the secondary data sources that the researchers used came from books, journals and theoretical articles, documents, and photos related to financial reports which discuss the Analysis of Decisions on the Financing of Hajj Bailout for Customers at PT. BPRS Metro Madani